THE EFFECT OF COOPERATIVE LEARNING METHODS WITH CONCEPT MAPPING LEARNING IN SPEAKING SKILLS ASSESSMENT - Nuraida, Ida; Halimah, Halimah; Saepuloh, Asep; Ningsih, Dinni Nurfajrin (Journal of Higher Education and Academic Advancement, 2024)
This paper describes how to applying the Cooperative Learning Method with concept mapping learning in English Language Education Department. The overall knowledge domain speaking in the field is shown. It is underlined that the concept mapping serves as a suitable tool to support instructors in promoting students’ skill of speaking and in improving their understanding of new concepts. This study examines the effect of concept mapping methods and assessment on the English speaking skills of students in English Education Department at Banten Jaya University. The results of the research testing described in the previous can be drawn: 1). There is an effect of the Cooperative Learning method with the Concept mapping to the fourth semester students speaking skill in English Education Department 2) There is an effect of Assessment on the English speaking skills of fourth semester students of the English Education Department. 3) There is an interaction between the Cooperative Learning method and concept mapping with assessment in Concept Mapping method in Speaking skill of fourth Student in English Education Department. From the three findings above, it can be concluded that the application of the method of learning English speaking skills must consider students' Speaking skill assessments